Impact of renal function on the safety of biologic and synthetic DMARDs in rheumatoid arthritis - Dilara Bulut Gökten; Ömer Atakan Soğur; Zoljargal Sukhbaatar; Ridvan Mercan (Medicine, 2026)
This study aimed to evaluate treatment patterns, adverse events, and drug discontinuations associated with conventional synthetic (csDMARDs), biologic, and targeted synthetic disease-modifying antirheumatic drugs in patients with rheumatoid arthritis (RA) and chronic kidney disease (CKD). A retrospective cohort study was conducted on 264 RA patients with CKD, followed between 2015 and 2025. Renal function was assessed using estimated glomerular filtration rate (CKD-epidemiology collaboration) and categorized according to Kidney Disease Improving Global Outcomes guidelines into stages 3 to 5. Demographic data, laboratory parameters, comorbidities, medication history, and all drug-related adverse events were collected. Severe adverse events were defined as those requiring hospitalization, causing drug discontinuation, or resulting in death. Comparisons among CKD stages were performed using chi-square, Fisher exact test, analysis of variance, or Kruskal–Wallis tests as appropriate. Of 264 patients, the median age was 65 years, and 73.9% were female. Hypertension and diabetes were the leading comorbidities and major contributors to CKD etiology. Use of nephrotoxic csDMARDs (methotrexate, leflunomide) and nonsteroidal anti-inflammatory drugs (NSAIDs) decreased with advancing CKD, whereas glucocorticoid use increased. Toxicity from methotrexate, leflunomide, and NSAIDs rose significantly across renal stages ( P < .05 for all). In contrast, adverse event rates for biologic disease-modifying antirheumatic drugs and targeted synthetic disease-modifying antirheumatic drugs did not differ significantly between CKD stages (all P > .05). No renal function-dependent increase in severe adverse events was observed for biologic or targeted therapies. In multivariable analysis, younger age, longer RA disease duration, higher baseline estimated glomerular filtration rate, and higher baseline Disease Activity Score 28-erythrocyte sedimentation rate were independently associated with the occurrence of any adverse event. While csDMARD and NSAID toxicity increase progressively with renal impairment, biologic and targeted synthetic agents maintain a stable safety profile across CKD stages.